The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1590/s0102-86502005000600003
|View full text |Cite
|
Sign up to set email alerts
|

Hypertonic saline and hemorrhagic shock: hepatocellular function and integrity after six hours of treatment

Abstract: Purpose:The comparison after 6h of hemorrhagic shock (HS) treatment with NaCl 7.5% (Hypertonic Saline Solution -SSH) or Ringer Lactate (RL) on liver function and integrity. Methods: Male Wistar rats were submitted to HS (Mean Arterial Pressure -MAP= 45 mmHg) during 60 min and then treated with NaCl 7.5% (SSH, 10% of blood loss, n=8) or Ringer Lactate (RL, 400% of blood loss, n=8). After 6h rats were anesthetized, hepatic function was assessed by bile flow measurement and liver integrity evaluated by determinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Previous study had shown that hypertonic saline with a colloid solution improved myocardial circulation in sepsis [25]. Hypertonic perfusion was also reported to reduce myocardial injury by reducing edema and diminishing calcium accumulation via decreasing Na/Ca exchange-mediated pathway during hypoxia [19,26]. Therefore, the enhanced myocardial anti-oxidative capacity in hyperosmolarityperfused hearts and enhanced coronary vasodilation may act in concert to reduce myocardial injury.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study had shown that hypertonic saline with a colloid solution improved myocardial circulation in sepsis [25]. Hypertonic perfusion was also reported to reduce myocardial injury by reducing edema and diminishing calcium accumulation via decreasing Na/Ca exchange-mediated pathway during hypoxia [19,26]. Therefore, the enhanced myocardial anti-oxidative capacity in hyperosmolarityperfused hearts and enhanced coronary vasodilation may act in concert to reduce myocardial injury.…”
Section: Discussionmentioning
confidence: 99%
“…It was soon realized that the physiological vasodilator property of hypertonicity was a useful byproduct of small volume resuscitation in that it induced reperfusion of previously ischemic territories. Subsequently, a number of researches disclosed previously unsuspected properties of HTS resuscitation, amongst them the correction of endothelial and red cell edema accompanying significant consequences in capillary blood flow (Victorino et al, 2003;Homma et al, 2005;Hoppen et al, 2005;Cruz et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, HTS resuscitation effectively ameliorates the cellular metabolisms by inducing a considerable microcirculatory improvement and restoring intestinal perfusion, which can reduce abnormal apoptosis of small intestinal mucosa (Murao et al, 2003;Shires et al, 2005). This positive effect of HTS is related to the correction of endothelial or red cell edema and selective vasodilation of the precapillary arteriole, accompanying significant consequences in capillary blood flow (Victorino et al, 2003;Vajda et al, 2004;Homma et al, 2005;Hoppen et al, 2005;Zakaria et al, 2006). Secondly, hemorrhagic shock causes a whole body ischemiareperfusion injury, leading to multiple organ dysfunctions.…”
Section: Discussionmentioning
confidence: 99%